Using Cooperation Science to Strengthen Maine’s Local Food Economy - Hupper, Afton; Chakraborty, Sujan; Waring, Timothy (Maine Policy Review, 2019)
While Maine’s food system has enjoyed a recent surge in demand for local food, this opportunity for economic growth has been impeded by a difficult business climate for farmers, small business owners, and institutions. We believe this difficult business climate necessitates policy interventions to sustain the local food economy. Cooperation science can be used to tackle the social dilemmas persisting in Maine’s local food economy and buttress the argument for increased support from the state. In this article, we implement the framework of cooperation to address the key concerns of farm viability, business succession, and increased food sourcing in local institutions from local producers in Maine.